Hubungan antara Kemandirian Belajar dengan Prokrastinasi Akademik pada Siswa SMA - Ayumi Ramadhita; Agus Tri Susilo; Citra Tectona Suryawati (Jurnal Psikoedukasi dan Konseling)
The study aimed to describe the level of independent learning and academic procrastination in high school students. The sampling technique in this study uses proportional random sampling with 203 samples. The data were collected using independent learning and academic procrastination scales. The hypothesis in this study used correlation and regression tests. The correlation test result showed a p-value of 0,000 and a correlation coefficient of -0,275. The regression test results showed that the effect of independent learning on academic procrastination is 80,9%, and the p-value was 0,000. The conclusion of this study is that there is a relationship between independent learning and academic procrastination, and independent learning has an impact of 80,9% on academic procrastination